2020
DOI: 10.3390/atmos11101042
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Built-Up Area Geometry on PM10 Levels: A Case Study in Brno, Czech Republic

Abstract: This paper presents a statistical comparison of parallel hourly measurements of particulatematter smaller than 10 μm (PM10) from two monitoring stations that are located 560m from each other in the northern part of Brno City. One monitoring station is located in a park, the otherin a built-up area. The authors’ aim is to describe the influence of a built-up area geometryand nearby traffic intensity on modeling of PM10 pollution levels in the respective part of Brno.Furthermore, the purpose of this study is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The authors pointed out that major parameters influencing the final shape of the PM 10 mass concentration field are wind direction and velocity, and the built-up area's geometry substantially modifies air flow velocity at the ground-level layers of the atmosphere. That the geometry of built-up areas is important for ambient PM 10 levels in cities is also supported by Neubauer et al [9], who studied hourly parallel records from two stations in Brno, one located in a park, the other one in a built-up area. The authors concluded that, apart from meteorology, this factor should definitely be accounted for in assessment of PM 10 pollution in densely populated urban areas with high levels of traffic.…”
Section: Aerosol Papersmentioning
confidence: 66%
“…The authors pointed out that major parameters influencing the final shape of the PM 10 mass concentration field are wind direction and velocity, and the built-up area's geometry substantially modifies air flow velocity at the ground-level layers of the atmosphere. That the geometry of built-up areas is important for ambient PM 10 levels in cities is also supported by Neubauer et al [9], who studied hourly parallel records from two stations in Brno, one located in a park, the other one in a built-up area. The authors concluded that, apart from meteorology, this factor should definitely be accounted for in assessment of PM 10 pollution in densely populated urban areas with high levels of traffic.…”
Section: Aerosol Papersmentioning
confidence: 66%